R v Hart: A New Common Law Confession Rule for Undercover Operations. (1st December 2014) - Hunt, Chris; Rankin, Micah
ABSTRACT: The Supreme Court of Canada's recent decision in R v Hart will be of interest to judges and criminal lawyers throughout the commonwealth. At issue in the case was the question of whether an accused could challenge the admissibility of a confession given in the course of 'Mr. Big' undercover police investigation (an elaborate undercover police investigations in which a suspect is misled into believing that he or she is being recruited into a fictitious criminal organisation.) In Hart, Canada's apex court broke sharply with its previous jurisprudence, creating a new, situation specific, common law rule of evidence. Henceforth, confessions obtained in the course of Mr. Big operations are presumptively inadmissible unless the Crown can prove the confession is reliable on a balance of probabilities. In this commentary, the authors argue that, while Hart is a welcome development in the law, commonwealth courts should be cautious in following the Supreme Court of Canada's approach. In the author's view, a better approach would be to modify the existing common law confession rule so that it applied to Mr. Big operations. Such an approach would produce greater certainty in the law and would afford greater protection for the accused.